Cloning, expression, purification, crystallization and preliminary X‐ray crystallographic study of thymidylate kinase (TTHA1607) from Thermus thermophilus HB8. Issue 2 (5th February 2013) - Chaudhary, Santosh Kumar; Jeyakanthan, Jeyaraman; Sekar, Kanagaraj
<x xml:space="preserve">Abstract</x> Nucleotide biosynthesis plays a key role in cell survival and cell proliferation. Thymidylate kinase is an enzyme that catalyses the conversion of dTMP to dTDP using ATP‐Mg2+ as a phosphoryl‐donor group. This enzyme is present at the junction of the de novo and salvage pathways; thus, any inhibitor designed against it will result in cell death. This highlights the importance of this enzyme as a drug target. Thymidylate kinase from the extremely thermophilic organism Thermus thermophilus HB8 has been expressed, purified and crystallized using the microbatch method. The crystals diffracted to a resolution of 1.83 Å and belonged to the orthorhombic space group P212121, with unit‐cell parameters a = 39.50, b = 80.29, c = 122.55 Å. Preliminary studies revealed the presence of a dimer in the asymmetric unit with a Matthews coefficient (VM) of 2.18 Å3 Da−1.